Brine Volume Fraction as a Habitability Metric for Europa's Ice Shell. Issue 22 (15th November 2022) - Wolfenbarger, N. S.; Fox‐Powell, M. G.; Buffo, J. J.; Soderlund, K. M.; Blankenship, D. D.
Abstract: Brine systems in Europa's ice shell have been hypothesized as potential habitats that could be more accessible than the sub‐ice ocean. We model the distribution of sub‐millimeter‐scale brine pockets in Europa's ice shell. Through examination of three habitability metrics (water activity, ionic strength, and salinity), we determine that brine pockets are likely not geochemically prohibitive to life as we know it for the chloride and sulfate‐dominated ocean compositions considered here. Brine volume fraction is introduced as a novel habitability metric to serve as a proxy for nutrient transport and recycling—because of its role in governing permeability—and used to define regions where nutrient‐open, nutrient‐closed, and relict habitats are stable. Whereas nutrient‐closed habitats could exist wherever brine is stable, nutrient‐open habitats are confined to meter‐scale regions near the ice‐ocean interface where freezing is occurring. This classification scheme can help guide future life‐detection missions to ocean worlds. Plain Language Summary: Pockets of salty liquid water (brines) could exist in the ice shell of Jupiter's moon Europa. Because brines would be stable over long timescales within these pockets, they represent places that could be inhabited by microorganisms. We model where sub‐millimeter‐scale brine pockets might exist in Europa's ice shell and then study the properties of the brine using a geochemical model. Our results demonstrate that the conditions of the brine do not fall beyond the limits of where life can exist on Earth, indicating that brine pockets may be suitable habitats in Europa's ice shell. We also model the amount of brine in the ice shell to see if organisms inhabiting these brine pockets could have access to ocean‐sourced nutrients via their transport along brine networks in the ice. By considering these factors, we classify potential brine habitats in Europa's ice shell. Key Points: Brine pockets in Europa's ice shell may not be geochemically prohibitive to life as we know it, and as such could be potential habitats Brine volume fraction, as a proxy for nutrient transport and recycling, may be a critical factor for the habitability of Europa's ice shell Ice shell habitats sustained by drainage of brine and recharge by ocean water (brine convection) can exist where the ice shell is freezing